Mechanisms of the Reversible Electrochemical Insertion of Lithium Occurring with NCIMs (Nano–Crystallite Insertion–Materials) - S. D. Han; N. Treuil; G. Campet; J. Portier; C. Delmas; J. C. Lassègues; A. Pierre (Active and Passive Electronic Components)
A new family of insertion-compound electrodes, so called NCIMs (Nano-Crystallite-Insertion-Materials) has been proposed: the major requirement is that the electrode materials have to be polycrystalline with a crystallite and particle size as small as possible (the accepted definition being that many crystallites make a particle). Indeed, by minimizing the size of the crystallites, the formation of defects is favored, particularly at the crystallite surface, acting as reversible (de)grafting sites of Li+. Also, the cation-anion bonding is weakened not only in the grain boundary region but also within the crystallite close to its surface: then the electrochemical insertion of Li+ takes place through easy bonding rearrangements.